The World’s First Clam Shrimp Symposium: Drawing Paleontology and Biology Together - Hegna, Thomas A. (Zool Stud, 2020)
After a symposium and special issue devoted to the study of clam shrimp, it is tempting to ask what is next... where is the study of clam shrimp going? Rather than try to read the tea leaves to predict the future, we will instead offer some closing thoughts on where the study of clam shrimp should go and what areas are ripe for investigation. Many of these ideas integrate both fossil and modern clam shrimp to get at a more complete view of their evolution and ecology.